KEMITRAAN ANTARA DESA DALANGAN DENGAN DESA JIMUS DAN DESA NGARAN DALAM PROGRAM PAMSIMAS - Sheilla Nur Setianingsih; Teguh Yuwono (Journal of Politic and Government Studies, 2018)
The Community Based Program on Water and Sanitation (PAMSIMAS) is one of the national programs to increase access of rural and peri-urban populations to provide water and sanitation facilities with a community-based approach. Implementation of this Pamsimas Program consists of three stages: Pamsimas I which was held in 2008-2013, Pamsimas II which was held in 2013-2016 and Pamsimas III implemented in 2013-2019. Pamsimas Program aims to provide water and sanitation for the people of Indonesia and is expected in 2019 has reached 100%. Accordingly the idea of partnership between Dalangan Village with Jimus Village and Ngaran Village, because Jimus Village and Ngaran Village do not have clean water while Dalangan Village has a spring.            Partnership between Dalangan Village with Jimus Village and Ngaran Village in pamsimas program can be said to be successful. The partnership between Dalangan Village and Jimus Village and Ngaran Village is good but no involvement of Dalangan Village community is in the planning process becoming a serious problem in the partnership because it will cause feelings of indifference to others. Another common problem is not getting involved in the formulation of the plan because it is only done by the board of the third pamsimas villages. In addition, that must continue also courage. Because it would be useless is the level of society is good but not balanced with the community activeness in the delivery of suggestions and criticism of the running of the partnership. In the management and sustainability of the partnership can be said to be effective and efficient because it is well organized starting from the frequency of meetings to the quality and quantity of meetings. The things that must be considered in implementing the partnership is the existence of an alternative fund. This research method use a mixed method to reveal in depth and the phenomenon of a phenomenon that will be studied by using Stratified Random Sampling method.            Recommendations for future partnership prospects are adding pipes so that all communities can feel the clean water from the partnership. Also do not forget to always control the pipes that connect the water from the Village Dalangan to Jimus Village and Ngaran Village in order to avoid severe damage.Keywords: Partnership, Clean Water, Community